Manuel L. Quezon and the Filipino women’s suffrage movement of 1937 - Alporha, Veronica C. (2022)
Access online through this link: https://www.plarideljournal.org/article/manuel-l-quezon-and-the-filipino-womens-suffrage-movement-of-1937
Keywords: Women's suffrage; Quezon, Manuel L., 1878-1944; Democracy